CALCULATION ALGORITHM FOR CONCRETE LONGEVITY BY GENERALIZED CRITERION - S. N. Leonovich (Nauka i Tehnika, 2009)
The paper describes problems pertaining to corrosion theory and forecast of reinforced concrete structure service life. The author considers that application of modern investigation methods on the basis of failure mechanics and analysis concrete porosity will make it possible to develop a general theory of concrete corrosion and calculation of reinforced concrete structure service life. Provision of the required longevity of reinforced concrete structures is not less important than the provision of their strength.